Modeling climate change effects on some biochemical parameters in horse - Deniz, Ömer; Aragona, Francesca; Pezzino, Gaetana; Cancellieri, Enrico; Bozaci, Serkan; Tümer, Kenan Çağrı; Fazio, Francesco (Elsevier BV, 2025)
Changes in the global climate pose a severe threat to human and animal welfare and productivity. Total proteins (TP), globulins (GLOB), albumins (ALB), alkaline phosphatase (ALP), creatine kinase (CK), lactate dehydrogenase (LDH), aspartate aminotransferase (AST), blood urea nitrogen (BUN), γ-glutamyl transferase (GGT), and creatinine (CREA) were evaluated during a three-year monitoring period (2021-23) on 16 Thoroughbred retired mares from the regional Golkoy Breeding Farm in Kastamonu- Turkey. The following thermal and hygrometric parameters were gathered: ambient temperature (AT), relative humidity (RH) and ventilation (VT), and the Temperature-Humidity Index (THI) was then calculated. Blood samples were collected on the first of each month from January 2021 to December 2023 and the obtained serum was used for the analysis, variations in environmental parameters were correlated to changes in biochemical profile. Two-way for repeated measure ANOVA showed a significant effect of month for AT (<0.0001), RH (<0.0001), and THI (<0.0001), and on TP (p < 0.001), GLOB (p < 0.001), ALB (p < 0.0001), ALP (p < 0.01), CK (p < 0.01), LDH (p < 0.001), AST (p < 0.0001), BUN (p < 0.0001), GGT (p < 0.0001), and CREA (p < 0.0001). ALP, CK, LDH, AST, and BUN values increased during the hottest periods, while GGT showed decreasing values during the summer. CREA showed positive correlation with AT, and LDH and CREA exhibited negative correlation with RH. These results may be useful for the monitoring of horses' physiological conditions as a result of climate change.
Keywords: Turkey; L-Lactate Dehydrogenase; Climate Change; Temperature; Humidity; Blood Proteins; Alkaline Phosphatase; Blood Urea Nitrogen; Creatinine; Biochemical profile Blood biomarkers Climate change Global warming Horse Seasons; Animals; Female; Horses; Aspartate Aminotransferases; Seasons; Creatine Kinase